Sample design of Portuguese National Health Examination Survey - Kislaya, Irina (2015)
This communication addresses problems arose and solutions adopted in sample design and sample selection for the first Portuguese National Health Examination Survey, a cross-sectional study that aims to obtain epidemiological data for the Portuguese population at regional and national level. The sample was based on two-stage stratified cluster design, with selection of geographical areas in the first stage and individuals in the second stage. Results suggest that sampling frame validation and use of multiple data sources in the survey planning stage are extremely important to minimize survey errors and selection bias.